Predicting Bystander Intention to Intervene: The Role of Gender-Specific System Justification and Rape Myth Acceptance for Men and Women - Martini, Mara; De Piccoli, Norma (Frontiers in Psychology, 2020)
The relationship between rape myth acceptance, gender-specific system justification, and bystander intention to intervene has often been studied on a one-dimensional, without separating the four dimensions of the acceptance of rape myths. The current study analyzes the relationship between the acceptance of rape myths, gender-specific system justification, and bystander intention to intervene, and explores whether the relationships operate differently for men and women. The sample was 3966 university students: 2963 from the University of Turin and 1004 from the Politecnico of Turin; 71.2% women and 28.8% men; average age 22.61 years. After descriptive analyses, independent sample T-test, and bivariate correlations, a model where the acceptance of four rape myths (“She asked for it”; “He didn’t mean to”; “It wasn’t really rape”; “She lied”) mediated the relationship between gender-specific system justification and bystander intention to intervene was tested on the whole sample and then separately on women and men. A bootstrapping procedure was applied. Our data show that for both men and women gender-specific system justification was related to the four rape myths, whereas women and men differed on the relationship between acceptance of rape myths and bystander intention to intervene: only the dimension “She asked for it” was significant for both groups; the dimension “It wasn’t really rape” was significant only for the men. Focusing on the differences in women and men regarding acceptance of rape myths can be fruitful for a theoretical deepening of the field and may inform the development of more successful prevention programs.